Forebrain NgR1 Overexpression Impairs DA Release Suggesting Synergy of Local and Global Synaptic Plasticity Mechanisms - Arvidsson, Emma; Gabulya, Sarolta; Brodin, Alvin Tore; Karlsson, Tobias Erik; Olson, Lars (Frontiers in Synaptic Neuroscience, 2020)
Structural synaptic re-organizations needed to permanently embed novel memories in the brain involve complex plasticity-enhancing and plasticity-inhibiting systems. Increased neural activity is linked to rapid down-regulation of Nogo Receptor 1 (NgR1), as needed to allow local structural synaptic plasticity. This local regulation of plasticity is thought to be moderated by global systems, such as the ascending cholinergic and monoaminergic systems, adding significance to locally increased neural activity. Here we address the reverse possibility that the global systems may also be influenced by the status of local plasticity. Using NgR1 overexpressing mice, with impaired plasticity and long-term memory, we measured the ability to release dopamine, implicated in regulating plasticity and memory. In vivo chronoamperometric recording with high temporal and spatial resolution, revealed severe impairment of KCl-induced increase of extracellular dopamine (DA) in dorsal striatum in mice overexpressing NgR1 in forebrain neurons. A similar, but lesser impairment of DA release was seen following amphetamine delivery. In contrast, KCl-evoked DA release in NgR1 knockout mice led to increased levels of extracellular DA. That NgR1 can impair dopamine signaling, thereby further dampening synaptic plasticity, suggests a new role for NgR1 signaling, acting in synergy with dopamine signaling to control synaptic plasticity.